Analysis Of Factors Determining Food Purchasing Decisions In Restaurant (Case Study at Marile Takoyaki Restaurant) - Ardiles, Muhammad Afung; Basauli Tambunan, Damelina (International Journal of Review Management Business and Entrepreneurship (RMBE), 2025)
The aim of this research is to analyze the factors determining food purchasing decisions through an Online Food Delivery application with the object being Marile Takoyaki Restaurant. The initial factors formed consist of 4 factors, namely price ratio, food quality, service quality, and website quality. The indicators used to explain the price ratio factor are food price, beverage price, and food portion. The food quality factor uses indicators such as delicious taste, nutritious food, the restaurant offering various menu items, the restaurant offering fresh food, very enticing food aroma, and visually appealing food presentation. The service quality factor uses indicators such as employees serving food exactly as ordered, quick and responsive service, employees always willing to help, and employees making customers feel comfortable dealing with them. The website quality factor uses indicators such as information quality, security, and payment system. The sample used in this research is 146 respondents using the purposive sampling method, with the condition that they have made a food purchase from Marile Takoyaki Restaurant through an Online Food Delivery application. This research uses factor analysis with SPSS as the analysis tool. The results of the research found that there are 3 factors determining purchasing decisions, namely, customer experience contributing 49.147%, customer satisfaction contributing 10.505%, and customer perception contributing 6.912%.